Pemanfaatan Vitamin C Untuk Meningkatkan Performa Imunitas Benih Ikan Gabus (Channa Striata) - sefti heza dwinanti; Ade Dwi Sasanti (Jurnal Akuakultur Rawa Indonesia, 2019)
Ascorbic acid was one of the important nutrients for fish because it has the property as an antioxidant and imunomodulator that can improve the performance of fish. The purpose of this research is to support the production of snakehead fish (Channa striata) that have good growth and immunity. This research used a complete randomized design (CRD) consisted of 3 treatments and 3 replications. Ascorbic acid treatment consisted of P1 (0 mg.kg-1), P2 (50 mg.kg-1) and P3 (100 mg.kg-1). The results showed that the maintenance of snakehead fish (Channa striata) given ascorbic acid  with a doses of 100 mg.kg-1  for 30 days gave the best growth results and significantly different and absolute weight growth reached 1.83 g, absolute length of 18.7 mm and survival reached 95 , 83 %. For immunity performance, it can be seen from survival of fish exposed to salinity 20 ppt during 15 minute reach 73,3 % and formalin 10 % for 10 minute reach 66,7 % and disease prevalence percentage reach 16,7 %